MANUSIA MEMPERDAGANGKAN MANUSIA? - William Chang; Lianto . (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2014)
A social trend that should trigger an emotional reaction in Indonesia as a nation that has enjoyed independence for the past 68 years, is none other than human trafficking. Indonesia is listed at 114 in the register of this modern form of slavery with around 220 thousand victims9 . Globally, there are around 29.8 million victims of human trafficking. Indonesia is one of the 17 source, transit and destination countries, involving criminal activities such as sex slavery, forced labour and child procurement. This situation is pretty evenly spread among all of Indonesia’s Provinces. The roots, the process and a way forward are highlighted in this brief study. Kata-kata Kunci: Human trafficking, perbudakan, migrasi, keluhuran matarbat manusia, hak asasi manusia.